“For the Record”: applying linguistics to improve evidential consistency in police investigative interview records - Haworth, Kate; Tompkinson, James; Richardson, Emma; Deamer, Felicity; Hamann, Magnus (Frontiers in Communication, 2023)
The 'For the Record' project (FTR) is a collaboration between a team of linguistic researchers and police in the England & Wales jurisdiction (E&W). The aim of the project is to apply insights from linguistics to improve evidential consistency in police interview transcripts, which are routinely produced by transcribers employed by the police. The research described in this short report is intended as a pilot study, before extension nationally. For this part of the project, we analysed several types of data, including interview audio and transcripts provided by one force. This identified key areas where current transcription practice could be improved and enhanced, and a series of recommendations were made to that force. This pilot study indicates that there are three core components of quality transcription production in this context: Consistency, Accuracy, and Neutrality. We propose that the most effective way to address the issues identified is through developing new training and guidance for police interview transcribers.